Management of rust red flour beetle (Tribolium castaneum) in stored sesame: Management of rust red flour beetle (Tribolium castaneum) in stored sesame - A K PANDAY; RAJANI BISEN; SURABHI JAIN; SUNDARIA M M; M CHANDRASEKARAN (Journal of Oilseeds Research, 2020)
Red rust flour beetle (Tribolium castaneum Herbst) is one of the major constraints of stored sesame in India. They damage the stored-sesame seed by feeding, and severely reducing the quality of seed due to product excrement and larval feces. Experiment was conducted to evaluate the persistency of chemicals and plant products to manage T. castaneum in stored sesame. The data revealed that spinosad 45SC was the most effective treatment and recorded highest mortality of adult beetles at 24th, 5th after release during first (83.75% and 100%), second (73.13% and 79.38%) and third months (68.75% and 80.63%) after release. NSK and neem leaf powder were also found effective and recorded 93.75 and 86.25%, 85 and 73.75% and 81.25 and 72.50% mortality of beetles at 25th day after release during1st , 2nd and 3rd months after release respectively.